PENGARUH PERSEPSI KEGUNAAN, PERSEPSI KEMUDAHAN PENGGUNAAN, PERSEPSI KENYAMANAN, TERHADAP PENGGUNAAN TRANSPORTASI BERBASIS ONLINE PADA GENERASI MILLENNIAL - Gusi Putu Lestara Permana; Kadek Wulandari Laksmi (Jurnal Widya Akuntansi dan Keuangan, 2019)
The aim of this research was to examine using of online transportation by millenials in Denpasar, The variables used in this research are based on technology acceptance model (TAM) stated by Davis (1989). The variables in this research was adaptable from this model, there are perceived usefulness, perceived ease of use and also add the new variable from motivational model are perceived enjoyment. The result of this research state perceived usefulness, perceived ease of use, and perceived enjoyment positively effect used of online transportation by millenials.